Study of correlation of ER, PR, HER2 receptor status in breast cancer at a single tertiary care hospital with emphasis on clinical utility of PR receptor - Shukla, Anjika; Singh, Poonam; Shukla, Anju; Mehrotra, Prateek Kumar; Arshad, Farah; Jain, Priyanka (International Journal Of Community Medicine And Public Health, 2018)
Background: The receptor status of breast cancer, including ER, PR and HER 2, play a crucial role in the development of treatment plan of breast cancer. Clinical utility of ER as a predictive biomarker to identify patients likely to benefit from hormonal therapy is well established, added value of PR is less defined. This study aim to know the demography of breast cancer and to document the status of ER, PR and HER 2 status in the north Indian population, as catered by single tertiary care hospital in Lucknow, Uttar Pradesh. Methods: All the patients of breast cancers where surgery or core biopsy was performed for invasive breast carcinoma followed by evaluation of ER, PR and HER 2 status were included in the study from January 2014 to June 2018. Cases were analyzed retrospectively for documentation of ER, PR and HER2 status, using American society of Clinical Oncology/College of American Pathologists (ASCO/CAP) interpretation guidelines. Results: 112 patients were included in the study with mean age of 53.70±12.47. Most common histological type was invasive carcinoma of no special type. 43.75% cases were ER+/PR+, 5.35% were ER+/PR-, and 50.89% were ER-/PR-. ER-/PR+ status was seen in none of our cases. Correlation of ER and PR with HER 2 was possible in 90 cases and triple negative breast cancer (TNBC) status was observed in 32.2% of cases. Conclusions: Demography and ER positivity and incidence of TNBC is not different from rest of India, however the clinical utility for evaluation of PR receptor is to be further investigated.